New record of the genus \(Dicamptus\) Szépligeti (Hymenoptera: Ichneumonidae: Ophioninae) from Vietnam - Thi Nhi, Pham; Vu Tru, Hoang; Thi Hoa, Dang; Van An, Dang (Academia Journal of Biology, 2022)
Dicamptus isshikii Uchida, 1928 is recorded for the first time from Vietnam on the basis of specimens collected from Bat Xat Nature Reserve, Lao Cai province, Northwest Vietnam. A checklist of the Dicamptus species of Vietnam is presented with detailed records on the distribution range of each species. A key to the Vietnamese species of the genus Dicamptus is also provided.